Pengaruh Kepuasan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT. Yun Kargo Indonesia - Sulastri Irbayuni; Christian Rico Yudi Pratama (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The existence of problems in terms of performance is a top priority in this research. This study aims: 1.) To determine the effect of job satisfaction on the performance of employees of the courier department at PT. Yun Cargo Indonesia; 2.) To determine the effect of work discipline on the performance of employees of the courier department at PT. Yun Cargo Indonesia. The data used in this study is primary data, namely data obtained through questionnaires distributed to employees of the courier department of PT. Yun Kargo Indonesia, which consists of 58 employees and the sample used is 58 respondents. The measurement uses an ordinal scale with a Likert scale weighting technique. The technique in taking the sample using a saturated sampling technique. While the analysis used in this study is Partial Least Square (PLS). PLS is a method for constructing predictable models when there are too many factors. The results of this study indicate that the higher the level of job satisfaction and work discipline, the higher the employee's performance. Keywords: Author Job Satisfaction, Work Discipline, Employee Performance.